Occupational exposure to Aflatoxin B1 in Portuguese swine farms - Viegas, Susana (2014)
In 1987, the International Agency for Research on Cancer concluded that there was sufficient evidence for carcinogenicity of naturally occurring aflatoxins in humans. Regarding occupational exposure to this chemical agent, farmers and other agricultural workers present a higher risk due to airborne aflatoxin via inhalation of dust. This study was carried out in 7 swine farms located at the district of Lisbon, Portugal. Blood samples were collected from a total of 11 workers. In addition, a control group (n = 25) was included that conducted administrative tasks in an educational institution without any type of agricultural activity. Results obtained suggest that occupational exposure to AFB1 by inhalation occurs and represents an additional risk in this occupational setting that need to be recognized, assessed and, most important, prevented.